(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
This article discusses the aesthetic relationships that permeate photographic production. In this sense, the paper provokes a reflection on the technical and mechanical transformations that condition the role of the photographic image as a mechanism for interpretation, recording, documentation, and – inevitably – construction of reality. From this conception, we seek to observe how digital structures influence and impact the image perception of reality. In this research, we will verify that the documentary character, evoked by the processes of analog photography, goes into a dynamic of emptying through digital appropriations, in order to propose a detachment from the concept of recording. In photography produced by Artificial Intelligence applications, we will analyze how the construction of images, through generative processes triggered as responses to user requests in common language, appropriates a repertoire made up of the reality experiences of other images, to create a window into an impossible dimension. Thus, this paper seeks to glimpse the process of breaking the documentary materiality of the photographic image, based on contemporary issues of the digital image.